Aminoazole-Based Diversity-Oriented Synthesis of Heterocycles - Murlykina, Maryna V.; Morozova, Alisa D.; Zviagin, Ievgen M.; Sakhno, Yana I.; Desenko, Sergey M.; Chebanov, Valentyn A. (Frontiers in Chemistry, 2018)
The comprehensive review contains the analysis of literature data concerning reactions of heterocyclization of aminoazoles and demonstrates the application of these types of transformations in diversity-oriented synthesis. The review is oriented to wide range of chemists working in the field of organic synthesis and both experimental and theoretical studies of nitrogen-containing heterocycles.